2023
DOI: 10.1002/cam4.5778
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin in cancer therapy: A pleiotropic tumoraffin nanocage‐based transport

Abstract: Background Ferritin, a ubiquitously distributed iron storage protein, can specifically target tumor cells through transferrin receptor 1. Due to its rearrangeable nanocage structure, ferritin can be loaded with anticancer drugs. Combined with amino acid modifications on the outer‐ and/or inner‐spaces of the nanocage, ferritins can be further coupled with antigens, antibodies, and nucleotide sequences. Since ferritin is naturally presented in the human body, when used in vivo, ferritin exhibits good biocompatib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 96 publications
0
1
0
Order By: Relevance
“…To address this limitation, researchers have developed dual-targeting ferritin drug carriers. For example, Deng et al (2023) genetically engineered a membrane-penetrating peptide called tLyP-1 and fused it to the N-terminal end of human ferrous ferritin (HFn). They loaded paclitaxel (PTX) into the HFn nanocage and demonstrated that this modified ferritin with tLyP-1 has dual receptor-mediated targeting function.…”
Section: Nanomedicine Carriers Involved In the Therapy Of Lung Cancermentioning
confidence: 99%
“…To address this limitation, researchers have developed dual-targeting ferritin drug carriers. For example, Deng et al (2023) genetically engineered a membrane-penetrating peptide called tLyP-1 and fused it to the N-terminal end of human ferrous ferritin (HFn). They loaded paclitaxel (PTX) into the HFn nanocage and demonstrated that this modified ferritin with tLyP-1 has dual receptor-mediated targeting function.…”
Section: Nanomedicine Carriers Involved In the Therapy Of Lung Cancermentioning
confidence: 99%
“…Generally, ferritin is a protein with a molecular weight of 450 kDa, consisting of 24 subunits self-assembled into a cage-like structure, with inner and outer sizes of 8 nm and 12 nm, respectively. 104–106 Ferritin derived from eukaryotes generally has two genes encoding the heavy chain and the light chain. The heavy chain and light chain subunits have different biological functions individually, and the proportion of heavy chain and light chain subunits in ferritin varies among different organisms and tissues, displaying distinct characteristics.…”
Section: Immunotherapy For Cancermentioning
confidence: 99%
“…HFn consist of 24 monomers of the H-chain of Fn characterized by a high thermal stability and low immunogenicity, as already reported by different groups, including ours. [13][14][15] Moreover, HFn can be loaded with drugs and fluorescent dyes for theranostic applications, following different approaches. The most common ones are the disassembly-reassembly induced by pH variation or by incubation with urea, and the opening of peculiar loading channels by increasing the temperature of the HFn solution.…”
Section: Introductionmentioning
confidence: 99%